Practices more likely to occur in kindergarten mathematics teachers' instruction when English learners are present. (June 2020) - Roberts, Sarah A.; Kirksey, J. Jacob; Gottfried, Michael
Abstract: Considering the rising proportion of English learners (ELs) in general education, little is known about how this change in classroom composition relates to the frequency of instructional activities and skills. This study uses a multimodal perspective on learning mathematics in a multilingual context, which recognizes the diverse modes of communication that students draw on in mathematics classrooms. We examined national data using quantitative analyses and investigated the mathematics practices that were more likely to occur in kindergarten classrooms that did and did not have ELs. We found teachers reported greater frequency of manipulatives and count/calendar activities in mathematics instruction when there were EL students in the classroom. Teachers in classrooms with ELs also reported a greater frequency of mathematics content that involved teaching shapes and practical skills. The findings indicate that teachers tended towards a supportive multimodal approach to instruction when ELs were present. Highlights: We study mathematics practices in kindergarten classrooms with an English learner. We utilized a US national data and quantitative analyses. Teachers used manipulatives and count/calendar activities more often with ELs. Teachers with ELs also taught more shapes and practical skills. Implications for educators and policy are discussed.